Cyclic characteristics of Macroeconomic Variables in Serbia - Zarić, Snježana M (Industrija, 2018)
The paper focuses on identification of the characteristics of the business cycles in Serbia. In that purpose, the empirical connection between the aggregate economic activity and key macroeconomic variables was examined, such as the GDP components, industrial production, employment, wages, price and monetary aggregates from the aspect of volatility, synchronization, and co-movements, as well as persistency. Also, the obtained results were compared to the results of similar researches in transition countries of the Central and Eastern Europe. Findings confirm the existence of significant regularities in movements of the analyzed economic time series compared to movements of the aggregate economic activity. Thus, the determined cyclical characteristics of the macroeconomic variables in Serbia do not deviate significantly from the so far documented characteristics in other European developing countries, even in respect of the differences compared to the developed countries
Keywords: Macroeconomics; Economics; Aggregation